Polypharmacy: definition, impact on outcomes, need for correction - S. Yu. Martsevich; N. P. Kutishenko; Yu. V. Lukina; O. M. Drapkina (Столичная издательская компания, 2023)
The review is devoted to a modern problem of polypharmacy. A universal definition and clear criteria for this concept have not yet been formed, but it is believed that this is the prescribing of at least 5 medications (M). The article discusses the frequency and main causes of polypharmacy, demonstrates its clear relationship with the age. The presence of overweight and obesity, multimorbidity, low physical activity, fragility are clearly associated with polypharmacy. Cognitive impairment, disability, long-term pain syndrome and malignant diseases also predispose to polypharmacy. The absence of a permanent attending physician, living in a nursing home, consulting with several specialists, poor management of medical records are associated with polypharmacy. It is believed that polypharmacy leads to a following number of adverse consequences: it increases the risk of falls, side effects of M, hospitalizations and even death. The main reason for this is the occurrence of various adverse interactions between M, including unpredictable ones, but the causal relationship of these phenomena with polypharmacy is not always proven. To study of adherence to prescribed therapy with polypharmacy is not an easy task, to date, there is no clear answer to the question whether polypharmacy affects adherence to drug therapy. The article presents in detail the problems of potentially irrational prescriptions, discusses the main methods of preventing and combating polypharmacy. Obviously, the most acceptable methods are the cancellation of drugs that are not indicated or contraindicated to the patient, and the prescribing of those drugs for which there are direct indications, but which the patient does not receive. The patient's therapy should be individualized as much as possible, taking into account numerous factors related to the peculiarities of the disease course, the prognosis, the patient's lifestyle, his physical and mental status.